An Edge Selection Mechanism for Chirally Selective Solubilization of Binaphthyl Atropisomeric Guests by Cholate and Deoxycholate Micelles. Issue 7 (14th June 2016) - Eckenroad, Kyle W.; Manley, Gregory A.; Yehl, Jenna B.; Pirnie, Ross T.; Strein, Timothy G.; Rovnyak, David
Abstract: Combining micellar electrokinetic capillary chromatography (MEKC) andnuclear magnetic resonance (NMR) experimentation, we shed light on the structural basis for the chirally selective solubilization of atropisomeric binaphthyl compounds by bile salt micelles comprised of cholate (NaC) or deoxycholate (NaDC). The model binaphthyl analyte R, S‐BNDHP exhibits chirally selective interactions with primary micellar aggregates of cholate and deoxycholate, as does the closely related analyte binaphthol (R, S‐BN). Chiral selectivity was localized, by NMR chemical shift analysis, to the proton at the C12 position of these bile acids. Correspondingly, MEKC results show that the 12α‐OH group of either NaC or NaDC is necessary for chirally selective resolution of these model binaphthyl analytes by bile micelles, and the S isomer is more highly retained by the micelles. With NMR, the chemical shift of 12β‐H was perturbed more strongly in the presence of S‐BNDHP than R‐BNDHP.Intermolecular NOEs demonstrate that R, S‐BNDHP and R, S‐BN interact with a similar hydrophobic planar pocket lined with the methyl groups of the bile salts, and are best explained by the existence of an antiparallel dimeric unit of bile salts. Finally, chemical shift data andintermolecular NOEs support different interactions of the enantiomers with the edges of dimeric bile units, indicating that R, S‐BNDHP enantiomers sample the same binding site preferentially from opposite edges of the dimeric bile unit. Chirality 28:525–533, 2016 . © 2016 Wiley Periodicals, Inc. Abstract : Aggregates of some bile salts are chiral selectors of certain atropisomeric binaphthyl guests. Using NMR in combination with MEKC, this work demonstrates that the S‐binaphthyl guest inserts in to a hydrophobic pocket more strongly from the carbon‐12 edge of antiparallel bile dimers than the R isomer, and that the bile 12α‐OH group is necessary for this chiral selection.